Digital Transformation in Banking: A Study of Student Adaptation in Sungai Penuh City in Migrating from BSI Mobile to Byond by BSI - Lubis, Mayang Sari; Mailindra, Wiyan (Jurnal Iqtisaduna, 2025)
The Islamic banking sector requires digital transformation to align with technological advances and consumer preferences. Bank Syariah Indonesia launched Byond by BSI to replace BSI Mobile, offering modern, secure features integrated with Islamic values. This study examines students’ adaptation in migration process, focusing on digital transformation, driving factors, and barriers. A descriptive qualitative method was applied through observation, in-depth interviews, and documentation involving twenty KIP-K recipients students in Sungai Penuh City based on Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). Results reveal all respondents responded positively due to superior design, comprehensive features, and enhanced security. Migration was driven by system pressure, institutional support, and perceived benefits. Barriers included technical issues and adaptation challenges. The findings confirm that successful digital banking migration requires clear policy, institutional support, and effective benefit communication.